2014
DOI: 10.1002/pd.4367
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical artery Doppler at 19 to 22 weeks of gestation in the prediction of adverse pregnancy outcomes

Abstract: Umbilical artery PI at 19 to 22 weeks of gestation is significantly associated with SGA below the tenth and fifth centiles. A multivariate model combining umbilical and uterine artery Doppler measurements with additional maternal and sonographic characteristics may help predict small for gestational age, particularly those below the fifth centile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…As we found that second‐trimester AC is the most important contributor to the statistical prediction of SGA, its inclusion in the multivariate model in that study could have led to different findings. Similar to our results, the ROC curve analysis for UtA and UA‐PI (AUC 0.55 and 0.60, respectively) and the reported screening characteristics of increased PIs suggested a limited predictive efficacy of second‐trimester Doppler indices for SGA …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As we found that second‐trimester AC is the most important contributor to the statistical prediction of SGA, its inclusion in the multivariate model in that study could have led to different findings. Similar to our results, the ROC curve analysis for UtA and UA‐PI (AUC 0.55 and 0.60, respectively) and the reported screening characteristics of increased PIs suggested a limited predictive efficacy of second‐trimester Doppler indices for SGA …”
Section: Discussionsupporting
confidence: 90%
“…But while a higher UA‐PI was associated with the risk of delivering an SGA infant, stronger associations were observed for measurements obtained in the third trimester . A more recent retrospective study exploring the association of second‐trimester Doppler parameters with subsequent adverse pregnancy outcomes found a significant independent contribution of UA‐PI in predicting SGA . However, fetal biometric parameters were not included in that analysis, and Doppler parameters were not normalized for gestational age.…”
Section: Discussionmentioning
confidence: 96%
“…Recent findings suggest that interrogation of fetal vessels at 20–24 weeks of gestation may also play a role in the identification of subsequent development of SGA. De Paco et al 27 conducted a large study addressing the performance of the umbilical artery during the second-trimester ultrasound scan. The authors measured the UA-PI in 4,565 fetuses at 19–22 weeks of gestation and reported that an UA-PI>90 th percentile was significantly associated with the delivery of an SGA neonate (birthweight <5 th and <10 th percentiles) with a likelihood ratio of 1.7 (95% CI, 1.2–2.4) for birthweight <10 th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, fetal Doppler evaluation has not been recommended before the suggested time for normal or reduced fetal growth screening at 24 weeks of gestation 26 . Recently, De Paco et al 27 explored the association between abnormal Doppler parameters obtained at 19–22 weeks of gestation and perinatal complications. The authors reported a 3.5 increment in the risk (95% confidence interval [CI], 1.7–7.1) for birthweight <5 th percentile in the presence of an abnormal umbilical artery pulsatility index (UA-PI) >90 th percentile.…”
Section: Introductionmentioning
confidence: 99%
“…Doppler blood flow measurement from the uterine artery is used for prediction of preeclampsia, hypertensive disorders in pregnancy, and as complementary surveillance parameters in high‐risk pregnancies and fetal growth restriction . A reference curve from normal pregnancies is the basis for identification of pathological blood flow.…”
Section: Introductionmentioning
confidence: 99%